The Vagaries of the Qaṣīdah - Montgomery, James Edward, 1962- (Oxfordshire)
vi, 296 s.
Keywords: "A study of the tradition and practice of early Arabic poetry, this book provides an investigation of the multiple versions of early poems that exist in various Abbasid collections. It offers a corrective to the more exaggerated claims concerning this poetry and revises some hitherto fundamental attitudes by advancing an individual philologically-driven vision of the period." --